Investigating the prevalence of malnutrition, frailty and physical disability and the association between them amongst older care home residents. (December 2020) - Fashho, Evate; Ahmed, Tanweer; Garden, Gill; Readman, Donna; Storey, Lesley; Wilkinson, Lindsey; Wilson, Graham; Slee, Adrian
Summary: Background: Malnutrition, frailty and physical disability are inter-related, more prevalent in the older population and increase the risk of adverse health outcomes. Thus, screening is essential, especially in the understudied care home setting where the population is vulnerable and at higher risk of malnutrition. Furthermore, prevalence may vary depending upon screening tools used. The aims of this study were to: 1) investigate the prevalence of 1) malnutrition risk using Mini Nutritional Assessment – Short Form (MNA-SF) and Malnutrition Universal Screening Tool (MUST), 2) frailty using the Edmonton Frailty Scale (EFS), 3) physical disability using the Barthel Index (BI) and (4) examine the association between variables and coexistence of states. Methods: Screening for malnutrition (MNA-SF and MUST) and frailty (EFS) was performed as part of a comprehensive geriatric assessment (CGA) in 527 residents from 17 care homes in Lincoln, UK. Mean age of the group was 85.6 ± 7.6 years and body mass index, BMI 23.0 ± 5.1 kg/m 2 . Results: A high prevalence of malnutrition risk was detected: 41.4% by MNA-SF and 25.5% by MUST (high risk/malnourished). Furthermore, there was a clear discordance between MNA-SF and MUST scoring of malnutrition; for example, the percentage of those identified as being at low risk was 18.8% using the MNA-SF and 57.0% using the MUST. In addition, there was a high prevalence of severe frailty by EFS (69.6%) and functional impairment by BI (62.0%). There was good association between some variables (P < 0.001) and 33.4% of residents had coexistence of all three states of malnutrition, frailty and physical disability. Conclusions: Malnutrition risk, frailty and physical disability are highly prevalent in care home residents and interrelated. However, prevalence varies depending on the screening tool used. More research should be conducted in the care home setting to improve daily clinical practice as screening may impact upon subsequent treatment and care modalities and clinical outcomes.